Once upon a cool motorcycle dude - O'Malley, Kevin, 1961-; Heyer, Carol, 1950-; Goto, Scott (New York : Walker, 2005)
Cooperatively writing a fairy tale for school, a girl imagines a beautiful princess whose beloved ponies are being stolen by a giant, and a boy conjures up the muscular biker who will guard the last pony in exchange for gold.
Publisher's Weekly
Bulletin (Center for Children's books)
Kirkus Review
3.6
3-6
Keywords: Authorship -- Juvenile fiction; Princesses -- Juvenile fiction; Motorcyclists -- Juvenile fiction; Humorous stories; Authorship -- Fiction; Princesses -- Fiction; Motorcyclists -- Fiction; Giants -- Fiction; Fairy tales; Humorous stories; Authorship -- Fiction; Princesses -- Fiction; Motorcyclists -- Fiction; Giants -- Fiction; Fairy tales; Humorous fiction